Detection of non-Einsteinian Gravitational Waves using a Pulsar Timing Array - Chamberlin, Sydney J. (Proceedings of the Wisconsin Space Conference, 2011)
In the next decade gravitational waves may be detected using a pulsar timing array. In an effort to develop optimal detection strategies for stochastic backgrounds of gravitational waves in general metric theories of gravity, we investigate the overlap reduction functions for these theories and discuss their characteristics. We show that sensitivity increases for non-transverse gravitational waves and discuss the physical origin of this effect. We calculate the overlap reduction functions for the current NANOGrav Pulsar Timing Array (PTA) and show that the sensitivity to the vector and longitudinal modes can increase dramatically for pulsar pairs with small angular separations.Â